2001
DOI: 10.1161/01.hyp.37.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Involvement in Renal Arteriolar Constrictor Responses to Angiotensin II

Abstract: Abstract-Experiments were performed to test the hypothesis that tyrosine kinase activity contributes to renal arteriolar contractile responses to angiotensin (Ang) II. Rats were subjected to short-term enalaprilat treatment to decrease endogenous Ang II formation before tissue was harvested for experiments with the in vitro blood-perfused juxtamedullary nephron technique. Acute surgical papillectomy was used to avoid the indirect afferent arteriolar effect of Ang II that arises through increased tubuloglomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…AG9, an inactive tyrphostin analog (IC 50 Ͼ1250 mol/L for EGFR tyrosine kinase), 27 failed to alter the [Ca 2ϩ ] i response to Ang II in the present study or the contractile response to Ang II in our previous study. 8 This observation is consistent with the idea that AG1478 suppresses the afferent arteriolar Ang II response through its ability to inhibit tyrosine kinase activity rather than through a nonspecific effect of tyrphostin compounds. Our observations extend to the renal microvascular level reports that tyrosine kinase inhibition attenuates Ang II-induced [Ca 2ϩ ] i and contraction responses in VSM cells from aorta or mesenteric artery.…”
Section: Che and Carmines Egfr And Ang II Signaling In Afferent Artersupporting
confidence: 87%
See 3 more Smart Citations
“…AG9, an inactive tyrphostin analog (IC 50 Ͼ1250 mol/L for EGFR tyrosine kinase), 27 failed to alter the [Ca 2ϩ ] i response to Ang II in the present study or the contractile response to Ang II in our previous study. 8 This observation is consistent with the idea that AG1478 suppresses the afferent arteriolar Ang II response through its ability to inhibit tyrosine kinase activity rather than through a nonspecific effect of tyrphostin compounds. Our observations extend to the renal microvascular level reports that tyrosine kinase inhibition attenuates Ang II-induced [Ca 2ϩ ] i and contraction responses in VSM cells from aorta or mesenteric artery.…”
Section: Che and Carmines Egfr And Ang II Signaling In Afferent Artersupporting
confidence: 87%
“…17,18 Moreover, we recently reported that renal arteriolar contractile responses to Ang II are suppressed by inhibition of EGFR tyrosine kinase activity. 8 The present study explored the …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vanadate-induced smooth muscle contraction (ileum) involves decreased activity of TyrP [Swarup et al, 1982] suggesting that TyrP activity modulates increased or decreased contractile activity of smooth muscle [Saifeddine et al, 1994]. In experiments in which angiotensin II was used to constrict the blood perfused afferent and efferent arterioles of juxtamedullary nephrons in young adult rats, broad spectrum blockade of TyrK reduced the constriction of those arterioles by 34% and 52%, respectively, demonstrating that reduction in TyrK activity reduces renal vascular constriction [Carmines et al, 2001]. When a TyrK inhibitor (AG1478) that specifically blocks the epidermal growth factor receptor (EGFR) TyrK was administered, the constriction to Angiotensin II in afferent and efferent arterioles was reduced 52% and 51%, respectively, suggesting that renal afferent arteriolar constriction to angiotensin II is most affected by the EGFR form of TyrK.…”
Section: Tyrosine Kinases Modulate G Protein Coupled Receptorsmentioning
confidence: 99%